A Research Framework for Business Models: What Is Common Among Fast Fashion, E-Tailing, and Ride Sharing? - Cachon, Gérard P. (Management Science, 2020)
Every firm has a business model, which is the collection of strategic decisions that determine how the firm generates a sustainable enterprise through the creation of enough value (its supply model) and the extraction of a sufficient portion of that value (its revenue model). Innovative business models—for example, fast fashion (e.g., Zara), e-tailing (e.g., Amazon), and ride-sharing (e.g., Uber)—are capable of offering new products and services that generate considerable consumer utility and transform industries. This paper develops a research framework for understanding business models and how business models have evolved over time. Links are made to the existing literature (primarily in pricing and operations), and simple models are developed to unify and clarify existing research findings. Through this framework, it is possible (i) to identify the few design decisions that explain the success of these diverse firms with otherwise seemingly disparate models, and (ii) to speculate on potential future business-model innovations. This paper was accepted by Teck Ho, operations management.